2011
DOI: 10.1159/000322806
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Dysregulation as a Core Feature of Borderline Personality Disorder: Comparison of the Discriminatory Ability of Two Self-Rating Measures

Abstract: Background/Aims: There is growing evidence that emotion dysregulation (ED) is a core feature of borderline personality disorder (BPD). The present study examines whether a self-rating measure, the ED Scale, lets us distinguish between individuals with BPD and those diagnosed with other mental disorders in a way similar to that of a borderline-related screening measure, the German version of the McLean Screening Instrument for Borderline Personality Disorders (MSI-BPD). Method: Based on the signal detection the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 88 publications
(55 reference statements)
0
10
0
3
Order By: Relevance
“…This might contribute to a lowered SENS value, assuming that PDs of the dramatic cluster could be well identified. Some evidence comes from findings in a similar outpatient sample, where a self-rated screening measure for borderline PD showed high diagnostic efficiency (SENS = 0.91; SPEC = 0.80) [45]. Third, generalization of our findings was limited to outpatients, considering that different base rates of PD and symptom spectrum, as expected in an inpatient setting, primary care, or the general population, have an impact on the ROCs of screening measures.…”
Section: Discussionmentioning
confidence: 83%
“…This might contribute to a lowered SENS value, assuming that PDs of the dramatic cluster could be well identified. Some evidence comes from findings in a similar outpatient sample, where a self-rated screening measure for borderline PD showed high diagnostic efficiency (SENS = 0.91; SPEC = 0.80) [45]. Third, generalization of our findings was limited to outpatients, considering that different base rates of PD and symptom spectrum, as expected in an inpatient setting, primary care, or the general population, have an impact on the ROCs of screening measures.…”
Section: Discussionmentioning
confidence: 83%
“…Beyond these aspects, ED also seems to have an effect on the severity and complexity of ADHD symptomatology as well as its comorbid disorders (Reimherr et al., ; Surman et al., ). ED is known to be present in other psychiatric conditions such as oppositional defiant disorder (Barkley, ; Reimherr et al., , ), borderline personality disorder (Carpenter & Trull, ; Kröger, Vonau, Kliem, & Kosfelder, ), mood disorders, (Aldao, Nolen‐Hoeksem, & Schweizer, ; Klassen, Katzman, & Chokka, ), anxiety disorders (Hofmann, Sawyer, Fang, & Asnaani, ), eating disorders (Merwin et al., ), and substance abuse/dependency (Bradley et al., ). These conditions often co‐occur with ADHD (Klassen et al., ) and make it unclear whether emotional symptoms could be seen as part of ADHD symptomatology.…”
mentioning
confidence: 99%
“…The initial validation with 200 gender-mixed subjects favored a cutoff point of 7 out of 10 items and yielded both good sensitivity (percentage of correctly identified BPD cases) and specificity (percentage of correctly identified non-BPD cases) (Zanarini et al, 2003). Various studies were conducted in different settings using the MSI-BPD: two inpatients studies (Kröger, Huget, & Roepke, 2011;Zanarini et al, 2003), three outpatient studies (Chanen et al, 2008;Kröger, Vonau, Kliem, & Kosfelder, 2011;Melartin, Häkkinen, Koivisto, Suominen, & Isometsä, 2009), and one sample from an ethnically diverse community (Patel, Sharp, & Fonagy, 2011). Overall these studies showed moderate to high diagnostic efficiency of the BPD-MSI, except for the inpatient study by Kröger, Huget, et al (2011), which revealed a very low specificity among non-personality disordered patients.…”
mentioning
confidence: 99%